Bank Sampah untuk Kesejahteraan dan Ekonomi Masyarakat di Desa Kota Daro II Ogan Ilir - Deassy Apriani; Bernadette Robiani; Imam Asngari; Feny Marissa; Sabillah Puteri Setiawan (Jurnal Pemberdayaan Ekonomi, 2022)
Purpose: The purpose is to create benefits from waste management to gain value-added. Furthermore, this activity will provide insight for the development of potential waste that has market value by managing it through a waste bank. Research methodology: The method used is to develop awareness/attitude for housewives regarding the value-added of waste with the target of approximately 20-30 respondens. This activity is carried out by direct meeting to the dedication site by communication and face-to-face interaction with villagers to seek cooperation in the activity. Result: The result of this activity is training on making eco-enzyme compost and utilizing waste into interesting handicrafts. Limitations: Rural communities still don’t know much about the use and management of waste that can be a blessing, so that in implementing long-term activities this is quite difficult to carry out. Contribution: The contribution of this activity, the Kota Daro villagers can be more independent and creative so that awareness, knowledge and skills are formed and eventually encourage participation in waste management in their environment.